Factors Influencing on decision making skill of executives of government sector service organization in Jaffna district - Yogendrarajah, R. (Modern Trends in Innovative Management (MTIM) at Rajarata University, 2011)
The focus of the study is to find out the impact of the factors which influence the Decision Making Skill of executives of Government Organization in the Jaffna District. Decision-making is the process of selecting one course of action from several alternative actions. Critical managerial decision making is the key to superior performance at work. Decision Making Skill of the Managers might be affected by various factors. This study addresses the influencing factors that are related to decision making, and categorizes them under five captions: Personal factors, organizational factors, Social factors, Environmental factors and behavioural factors. The prime Objective of this study was to identify the decision making skill of the executives and what are the factors that influence on their decision making. The central research question here is “what are the factors influencing the decision making of the executives”. To answer this question the data were gathered from the executives from top, middle and lower level in 15 Government Service organizations out of 55 under the Provincial Council in Jaffna District. A total number of fifty(50) Decision Making Questionnaires (DMQ) were issued but thirty seven (37) responded. Statistical Package for Social Sciences (SPSS) method of data analysis was used to find out the results and it was discovered that the environmental factors and organizational factors have more significant influence on decision making than the other factors that are personal, social and behavioural factors.
Keywords: Decision making skill; Personal factors; Cultural factors; Environmental factors; Beavioural factors; Social factors